Ulirang pamilihan redifining market zones through a cultural and robust Philippine weekend market - Ting, Joshua Lance D.; Dul-loog, Vic L.; Galingan, Zenaida C. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
Markets are cultural centers of a place. They are important factors in the urban fabric; sustaining the needs of the community as well as being a space of recreation. The multi-purpose nature of markets makes them dynamic spaces that transforms with its users. Weekend markets play such purpose and showcase an area that's more mixed-used than other markets. It serves a different function, such as a park, throughout the weekday and a market by weekend. Markets are part of our daily lives and will stay that way for a long time. These days, in the Philippines, such spaces are subjected to degradation due to the focus of profit and individual economic gain. People forget the importance of markets and how these reflect the culture of a place; being a place convenience and pleasure of all its users as well as being a cultural urban center. Marketplaces does not only encompass economics but it can also be analyzed through different fields such as psychology, culture, geography, anthropology, history and business. The research proposed a landscape design of a vibrant and robust weekend market that could be a tourist destination and exhibit Filipino culture. Revitalizing marketplaces in the country by making it Filipino; incorporating the traditional values and roots to bring forth a space that understands Filipinos and a space Filipinos understand. Because what can Filipinos contribute to the world the best other than being Filipino itself?
includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman